ANALISIS CAPITAL ADEQUACY RATIO, FINANCING TO DEPOSIT RATIO, NON PERFORMING FINANCING, DAN DANA PIHAK KETIGA TERHADAP TINGKAT PROFITABILITAS BANK UMUM SYARIAH PERIODE 2011-2013 - Nurul Mahmudah; Ririh Sri Harjanti (Prosiding Seminar Nasional IPTEK Terapan (SENIT) 2016 Pengembangan Sumber Daya Lokal Berbasis IPTEK, 2016)
This study aimed to analyze the effect of capital adequacy ratio (CAR), Financing to Deposit Ratio (FDR), Third Party Fund (DPK), and the level of revenue sharing on profitability (ROA) of Islamic commercial bank that operates in Indonesia from 2011-2013. As well as to analyze the effect of Non Performing Financing (NPF) to profitability (ROA) of Islamic banks operating in Indonesia from 2011-2013. The population in this study is an Islamic commercial bank registered in Bank Indonesia within 2011-2013 research. Tests carried out using multiple linear regression. The test results showed that the Capital Adequacy Ratio (CAR) significant positive effect on ROA. FDR (Financing Debt Ratio), Third Party Fund (DPK), and the level of revenue sharing is effect on ROA. As well as nonperforming financing (NPF) no effect on ROA. Keywords: Capital Adequacy Ratio, Financing to Deposit Ratio, Non Performing Financing, Third Party Funds, And Levels For Results and Profitability